2006
DOI: 10.1590/s1135-57272006000500005
|View full text |Cite
|
Sign up to set email alerts
|

La epidemiología en la salud pública del futuro

Abstract: The evolution of epidemiology from a risk factor centred approach to a population epidemiology, focused in etiologic theories and more connected with the social and environmental context could support but not guarantee the implementation of public policies oriented to improve population health. In this article, we comment on several factors that, from the research, professional and health services viewpoints, could determine a better linkage between epidemiology and public health policies. Creativity and innov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 16 publications
0
6
0
6
Order By: Relevance
“…In turn, indicated that sexual solicitation by adults predicted an increase in sexualized interactions with adults one year later. In general, the scarcity of longitudinal studies has meant that there is no epidemiological evidence of this problem over time; that is, there have been no indicators such as period prevalence (the number of cases of an event during a period of time) or incidence (new cases in a given population in a given period) of this problem (Hernández-Aguado & Lumbreras, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In turn, indicated that sexual solicitation by adults predicted an increase in sexualized interactions with adults one year later. In general, the scarcity of longitudinal studies has meant that there is no epidemiological evidence of this problem over time; that is, there have been no indicators such as period prevalence (the number of cases of an event during a period of time) or incidence (new cases in a given population in a given period) of this problem (Hernández-Aguado & Lumbreras, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Bayesian methodology appears a more than viable option in the study of rare and low incidence diseases (Hernández-Aguado et al, 2006;Zurriaga Llorens et al, 2006). Prior information should be used to improve the effi ciency of the method and, therewith, the results (Bayarri & Cobo, 2002;Álamo, Vázquez & Rodríguez, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…This is especially so in epidemiological sciences, that are ranging over a much larger fi eld larger than before, focusing on the study of risk factors in the population with a view to developing population health policies (Hernández-Aguado, Lumbreras & Jarrin, 2006;Nettleton, Woods, Burrows & Kerr, 2009). Health professionals are particularly interested in developing methodologies for a better study of diseases, especially rare and low-incidence diseases, in general and in endemic cases.…”
mentioning
confidence: 99%
“…Como se señaló anteriormente, deberían considerarse otros valores además de la autonomía, como la beneficencia, la solidaridad y la subsidiariedad, pues un límite racional de la autonomía es prevenir el daño propio y el de terceros; así mismo, es necesario entender que el término 'bienestar' en medicina tiene un campo bien definido en el orden salud/enfermedad (36).…”
Section: El Concepto Subjetivo De Autonomíaunclassified